2007
DOI: 10.1039/b705666d
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer pathways in the carbazole functionalized β-diketonate europium complexes

Abstract: Two novel Eu 3+ complexes Eu(CDBM) 3 Á 2H 2 O and Eu(CCDBM) 3 Á 2H 2 O have been synthesizedshowed strong internal ligand charge transfer (ILCT) fluorescence and sensitized emission of Eu 3+ . Due to the charge transfer character, the fluorescence band of CDBM shifted from 403 nm in cyclohexane to 559 nm in acetonitrile. Photophysical studies demonstrated that no energy was migrated from the ILCT excited state of the ligands to Eu 3+ , and that Eu 3+ was sensitized by the triplet state which was localized in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…One may consider HL-NMe 2 as an analogue of Michler's ketone (Scheme 2) -a push-pull chromophore, which was shown to be an excellent sensitizer of lanthanide luminescence. [27] In fact, similar 1,3-diketones containing 4-(dialkyl-or diarylamino)phenyl groups reported in the literature [15,26,[28][29][30][31][32] also display a low-energy absorption band which was shown by spectroscopic measurements [26,28] and calculations [31] to be of a charge-transfer nature. In comparison, the lowest-energy absorption transition in dibenzoylmethane and bis(p-nitrobenzoyl)methane -model 1,3-diketones which do not contain donor groups -occurs in the onset of the UV range at 352 nm and 362 nm, [17] .…”
Section: Photophysical Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…One may consider HL-NMe 2 as an analogue of Michler's ketone (Scheme 2) -a push-pull chromophore, which was shown to be an excellent sensitizer of lanthanide luminescence. [27] In fact, similar 1,3-diketones containing 4-(dialkyl-or diarylamino)phenyl groups reported in the literature [15,26,[28][29][30][31][32] also display a low-energy absorption band which was shown by spectroscopic measurements [26,28] and calculations [31] to be of a charge-transfer nature. In comparison, the lowest-energy absorption transition in dibenzoylmethane and bis(p-nitrobenzoyl)methane -model 1,3-diketones which do not contain donor groups -occurs in the onset of the UV range at 352 nm and 362 nm, [17] .…”
Section: Photophysical Propertiesmentioning
confidence: 91%
“…[7][8][9] One of the challenges in the design of luminescent lanthanide tags, particularly those aimed at bioanalyses and bioimaging, is to shift the excitation wavelength from the UV to the visible range, for both an intrinsic reason, since biomolecules are usually damaged by UV light, and a practical one, visible excitation requiring cheaper optical cells and optics. Several strategies have been proposed towards this goal, for instance excitation through d-metal ions, [2,4,10] by multiphoton excitation, [11][12][13][14] or via ILCT states [7][8][9]15] which may have relatively low energy. For instance, we recently showed that energy can be transferred from bodipy (a boradiazaindacene-appended terpyridine at 400-550 nm which was utilized to achieve visible-light excitation of metal-centred infrared luminescence of Nd III with maximum absorption at 529 nm) to Nd III , Er III , and Yb III .…”
Section: Introductionmentioning
confidence: 99%
“…230 and 260 nm) units are overlapped with the much stronger carbazole features. [26] However, although in the high-energy spectral region (λ Ͻ 300 nm) carbazoleselective excitation may be accomplished (Ͼ90 %, Figure 1), the light partitioning around 350 nm is approximately 65 and 35 % for the carbazole and β-diketonate moieties, respectively. For both Eu·dbm·carb·bath and Eu·dbm·carb·phen, the typical Eu III ion luminescence spectrum peak at 612 nm was detected in dichloromethane solution upon exciting at 264 and 350 nm (Table 1), respectively.…”
Section: Absorption and Emission Propertiesmentioning
confidence: 99%
“…According to the photosensitized luminescence of lanthanide(III) complexes accelerated by intra-LCT, Eu(III), Yb(III), Nd(III), and Er(III) complexes with donor amineattached diketonate ligands have been reported (Φ π−π* : Nd = 0.0078%, Yb = 0.04%, Fig. 7a) 41,42 . The effective luminescence of lanthanide(III) complexes with donor pyridine-attached ligands has been reported (Φ π−π* : Eu = 43%, Nd = 0.22%, Yb = 0.59%, Fig.…”
Section: Effect On Ct Bandmentioning
confidence: 99%